The perioperative outcomes between renal hilar and non‐hilar tumors following robotic‐assisted partial nephrectomy (RAPN). Issue 8 (August 2018) - Lu, Shih‐Yen; Chung, Hsiao‐Jen; Huang, Eric Yi‐Hsiu; Lin, Tzu‐Pin; Lin, Alex T.L.
Abstract : Background: : The aim of this study was to compare the perioperative outcomes between renal hilar tumors and non‐hilar tumors after robotic‐assisted partial nephrectomy (RAPN). Methods: : A retrospective review of consecutive patients who underwent RAPN from December 2009 to September 2015 at our institution was recruited. Perioperative outcomes including demographic characteristics, perioperative, pathological and renal function outcomes were compared between the hilar group (n = 30) and non‐hilar group (n = 170). Results: : In characteristics, hilar group was younger (52.4 vs. 58 years, p = 0.04) and had less body mass index (23.7 vs. 25.4 kg/m 2, p = 0.018). Hilar group had larger tumor size (4.8 vs. 3.7 cm, p = 0.009), higher Preoperative Aspects and Dimensions Used for an Anatomical (PADUA) score (10.7 vs. 8.5, p < 0.001) and higher RENAL (radius, exophytic/endophytic properties of the tumor, nearness of tumor deepest portion to the collecting system or sinus, anterior/posterior description and the location relative to polar lines) score (9.0 vs. 7.4, p < 0.001). Hilar tumor was associated with longer operative time (293.6 vs. 240.5 min, p = 0.001) and warm ischemia time (39.9 vs. 21.8 min, p < 0.001). But there was no statistically difference in estimated blood loss (EBL), postoperative stay and complication rate. For pathological outcomes, there was no difference of positive margin rate and pathological T stage between these groups. For renal function outcomes, hilar tumor patients had no difference of the change of creatinine and estimated glomerular filtration rate (eGFR) at postoperative 6 and 12 month as compared with non‐hilar tumor patients. Conclusion: : For renal hilar tumor, RAPN could provide acceptable results of perioperative, pathological and renal function outcome as compared with non‐hilar tumor group. Thus RAPN is a safe and effective nephron‐sparing surgery technique for renal hilar tumors.